2016
DOI: 10.1016/j.vph.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic acid-evoked Ca2+ signals promote nitric oxide release and proliferation in human endothelial colony forming cells

Abstract: Arachidonic acid (AA) stimulates endothelial cell (EC) proliferation through an increase in intracellular Ca concentration ([Ca]), that, in turn, promotes nitric oxide (NO) release. AA-evoked Ca signals are mainly mediated by Transient Receptor Potential Vanilloid 4 (TRPV4) channels. Circulating endothelial colony forming cells (ECFCs) represent the only established precursors of ECs. In the present study, we, therefore, sought to elucidate whether AA promotes human ECFC (hECFC) proliferation through an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
109
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 53 publications
(121 citation statements)
references
References 97 publications
12
109
0
Order By: Relevance
“…Previous studies showed the intracellular levels of NAADP may be increased by using NAADP-encapsulating liposomes. This finding, along with the observation that the NAADP-gated TPC1 is expressed in ECFCs [Zuccolo et al, 2016b], confirmed that PL formulations were suitable to load these cells with NAADP, thereby activating its prominent downstream signaling pathway, that is, intracellular Ca 2þ mobilization. The formulations were prepared by dissolving NAADP within a KCl buffer.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Previous studies showed the intracellular levels of NAADP may be increased by using NAADP-encapsulating liposomes. This finding, along with the observation that the NAADP-gated TPC1 is expressed in ECFCs [Zuccolo et al, 2016b], confirmed that PL formulations were suitable to load these cells with NAADP, thereby activating its prominent downstream signaling pathway, that is, intracellular Ca 2þ mobilization. The formulations were prepared by dissolving NAADP within a KCl buffer.…”
Section: Discussionsupporting
confidence: 60%
“…This finding reinforces the notion that the surface charge has a crucial role in permitting liposomes to be internalized into the cell. The involvement of NAADP receptors, that in ECFCs are represented only by TPC1 [Zuccolo et al, 2016b], was probed with NED-19, a specific blocker of NAADP-induced Ca 2þ release [Morgan et al, 2011;Ronco et al, 2015]. 4B), while empty liposomes did not alter intracellular Ca 2þ levels (not shown).…”
Section: Naadp Containing Liposomes Increase [Ca 2+ ] I In Ecfcsmentioning
confidence: 99%
“…Recent studies have also revealed the presence of intracellular two-pore channels (TPCs) in endothelial cells that belong to a family of the voltage-gated ion channels [192], [193], [194]. The family is presented by three distantly related proteins (TPC1–3) with TPC2 specifically localized to the lysosomal, and TPC1 to the endolysosomal systems [192], [195].…”
Section: Introductionmentioning
confidence: 99%
“…In endothelial cells, TPCs are mainly involved in regulation of cell proliferation [193], [194]. TPC2, which promotes Ca 2+ release from lysosomal stores, potentiates pro-angiogenic effect of Vascular Endothelial Growth Factor (VEGF) on endothelial cells, suggesting a specific role of TPC2 in VEGFR2-mediated angiogenesis [193].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation